Psychiatric Morbidity in Ketamine Users Attending Counselling and Youth Outreach Services. Issue 1 (January 2015) - Tang, Wai Kwong; Morgan, Celia J. A.; Lau, Grace C.; Liang, Hua Jun; Tang, Alan; Ungvari, Gabor S.
Background: No study has examined ketamine users' psychiatric morbidity using structured diagnostic instruments. The aim of this study was thus to determine the psychiatric comorbidity of community-based ketamine users using the Structured Clinical Interview for DSM-IV ( Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition ), Axis I Disorders (SCID). Methods: A convenience sample of 200 frequent ketamine users was recruited from community organizations in Hong Kong. Participants were screened with the Severity of Dependence Scale (SDS), Beck Depression Inventory (BDI), Anxiety subscale of the Hospital Anxiety Depression Scale (HADSA), and SCID psychotic symptoms. Those who scored above the threshold (cutoff point of 8/9 on the BDI and 4/5 on HADSA) or displayed evidence of psychotic symptoms were referred for a structured clinical interview conducted by a psychiatrist. Results: One hundred and seventy participants scored above the cutoff point on 1 or more of the scales, and 115 participants attended the SCID interview. Fifty-one of these 115 participants received a psychiatric diagnosis of 1 or more comorbidities for the month preceding the interview. Mood disorders accounted for 80.4% of the diagnoses, anxiety disorders for 33.3%, and psychotic disorders for 7.8%. Conclusions: Female gender and history of psychiatric/psychological clinic attendance were significantly associated with comorbid psychiatric disorders, whereas ketamine dependence had a borderline association.